POLA KOMUNIKASI PEMELUK AGAMA DALAM MENJAGA KERUKUNAN UMAT BERAGAMA DI DUSUN BINANGA-BENTENG DESA BINANGA SOMBAIYA, KEC. BONTOSIKUYU, KAB. SELAYAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This research is research using a qualitative approach. This study aims to explain the series of occurrences of the phenomenon of changing religions, then the factors behind someone changing religions. This research was conducted in Binanga Sombaiya Village, Binanga-Benteng Hamlet, Selayar Islands Regency. The data collection techniques used were observation and interviews with related informants, the history of different religions, the factors behind someone changing religions. The results showed that the phenomenon of religious conversion was due to the entry of a sect called Muhdi Akbar. Keywords: History, Change of Religion, Muhdi Akbar